Nova kakovost, ki jo prinaša strukturiran zapis v dokumentiranju zdravstvene nege - Šušteršič, Olga (Obzornik zdravstvene nege, 2000)
Documentation is an important element of modern nursing care, assuring continuity, reflecting professionalism and offers a basis for evaluation of nursing care. Successful decumentation is an esential part of the process method of work, including evaluation of a client's and patient's health status. It represents the basis for the definition of nursing problems, diagnoses and planning of nursing care. The change and progress in health status is an indicator of a successful nursing process. Into the hierarchical structure of indicators of the holistic evaluation and fourteen life activities of a patient measurement scales of five descriptive values and aggregation functions are introduced. The process method of work id thus complemented with additional practically applicable cybernetic solution with feed back evaluation which is an important element of the treatment of nursing phenomena in the presentation of knowledge in health field.
Keywords: Dokumentacija; Nursing care; Nursing records; Zdravstvena nega